Solvent-Driven Variations of Third-Order Nonlinear Thermo-Optical Features of Glutaric Acid-Directed Self-Healing Supramolecular Ni(II) Metallogels - Pal, Indrajit (Langmuir : the ACS journal of surfaces and colloids, 2023)
The generation of solvent-directed self-healing supramolecular Ni(II) metallogels of glutaric acid (i.e., Ni-Glu-DMF and Ni-Glu-DMSO) is described in this article. Polar aprotic solvents like N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are separately entrapped into the Ni(II)-acetate salt and glutaric acid-mediated networks to attain the semisolid flexible scaffolds. The gel nature of the fabricated materials is experimentally proven through different rheological tests such as amplitude sweep, frequency sweep, and thixotropic (time sweep) measurements. The self-repairing strategy and load-bearing features of the synthesized metallogel are studied in this work. The different supramolecular noncovalent interactions working within the soft scaffold are clearly explored. The formation strategy and the microstructural features of these synthesized metallogels are scrutinized through a Fourier transform infrared (FT-IR) spectroscopy study and field-emission scanning electron microscopy (FESEM) morphological analyses. The FT-IR spectroscopy observation displays a considerable amount of shifting of the infrared (IR) peaks of the xerogel samples of both the metallogels Ni-Glu-DMF and Ni-Glu-DMSO. The electrospray ionization (ESI)-mass spectroscopy result demonstrates the plausible construction of the metallogel network. In order to examine the nonlinear optical characteristics of the two synthesized self-healing metallogels Ni-Glu-DMSO and Ni-Glu-DMF, Z-scan measurements are carried out with a continuous wave (CW) diode-pumped solid-state (DPSS) laser at 532 nm. The nonlinear refractive index, nonlinear absorption coefficient, thermo-optical coefficient, and third-order susceptibility of these metallogels were evaluated by analyzing the experimental data from the Sheik-Bahae formalism. The nonlinear thermo-optical study reveals that these solvent-dependent metallogels show negative signs of nonlinear refractive index and nonlinear absorption coefficient. The figure of merit calculated for these compounds shows good agreement for their use in nonlinear photonic devices